2015
DOI: 10.1039/c5cc02901e
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-difluoro(oxalato)borate (NaDFOB): a new electrolyte salt for Na-ion batteries

Abstract: Compatible with various common solvents, a new electrolyte salt NaDFOB has been studied, which enables excellent reversible capacity and high rate capability when used in Na/Na0.44MnO2 half cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…39 A systematic study on the electrochemical stability of electrolytes at various temperatures is important. The specic decomposition potentials of some signicant electrolytes are summarized in the literature; [65][66][67][68][69][70] these studies have shown that solvent systems, type of salt, and working electrodes all affect the electrochemical stability window.…”
Section: Electrochemical Stabilitymentioning
confidence: 99%
“…39 A systematic study on the electrochemical stability of electrolytes at various temperatures is important. The specic decomposition potentials of some signicant electrolytes are summarized in the literature; [65][66][67][68][69][70] these studies have shown that solvent systems, type of salt, and working electrodes all affect the electrochemical stability window.…”
Section: Electrochemical Stabilitymentioning
confidence: 99%
“…It will also not generate toxic or dangerous products when exposed to air and water, indicating that NaDFOB may be a prospective Na salt for application in high performance electrolytes for future SIBs. 271 A new high-voltage electrolyte was developed from NaClO4 in mixed ethyl methanesulfonate (EMS) and FEC. 272 The anodic stability of this electrolyte could be increased to 5.6 V vs. Na + /Na, which is higher than that of the PC-based electrolyte of 4.5 V. Moreover, the EMS-based electrolyte had a slightly higher ionic conductivity of 6.3 mS cm ─1 at 25 o C. In this high-voltage electrolyte, the 4.0 V positrode of Na[Ni0.25Fe0.5Mn0.25]O2 was found to have much improved electrochemical performance.…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…To improve the coulombic efficiency of the current SIBs, NaDFOB salt was tested with EC/DMC solvent. 382 The salt was prepared from the reaction of sodium oxalate ( Figure 34e). In this test, the NaDFOB-based electrolyte exhibited a high coulombic efficiency (close to 100%) and long cycle life with low capacity fade.…”
mentioning
confidence: 99%